Rancang Bangun Sistem Pendeteksi serta Pengusir Tikus Menggunakan Stimulus Auditori dan Visual pada Lahan Pesawahan Berbasis Mikrokontroler - Putra, Riski Mai; Almasri, Almasri; Jaya, Putra; Fikri, Ryan (Lembaga Yasin AlSys, 2026)
Rats are one of the main causes of reduced rice production in Indonesia because they attack crops at various growth stages, whereas the control methods commonly used by farmers, such as chemical poisons and mechanical traps, are considered less effective in the long term and have the potential to cause negative environmental impacts. This study aims to design and develop a rat detection and repellent system using a combination of auditory stimuli in the form of ultrasonic waves and visual stimuli in the form of strobe lights based on a microcontroller. This system uses Arduino UNO as the main controller integrated with Passive Infrared (PIR) sensors and ultrasonic sensors to detect the presence of rats. The research method included the stages of needs analysis, system design, hardware and software implementation, and system testing in a rice field environment. The test results showed that the system was able to operate automatically and effectively repel rats through a combination of sound and light stimuli without using hazardous chemicals. These findings affirm that the designed system has the potential to become an alternative solution that is environmentally friendly, energy-efficient, and easy to operate in supporting rat pest control in rice fields.